2010
DOI: 10.48550/arxiv.1010.3657
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Inflation in Supersymmetric SU(5)

S. Khalil,
M. U. Rehman,
Q. Shafi
et al.

Abstract: We analyze the adjoint field inflation in supersymmetric (SUSY) SU (5) model. In minimal SUSY SU (5) hybrid inflation monopoles are produced at the end of inflation. We therefore explore the non-minimal model of inflation based on SUSY SU (5), like shifted hybrid inflation, which provides a natural solution for the monopole problem. We find that the supergravity corrections with non-minimal Kähler potential are crucial to realize the central value of the scalar spectral index n s ≃ 0.96 consistent with the sev… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(32 citation statements)
references
References 23 publications
0
32
0
Order By: Relevance
“…If the gauged supermultiplets are in the adjoint representation, the leading order non-renormalizable term is cubic in Φ. For a detailed analysis of shifted inflation with an SU(5) GUT, see Ref [17]…”
mentioning
confidence: 99%
“…If the gauged supermultiplets are in the adjoint representation, the leading order non-renormalizable term is cubic in Φ. For a detailed analysis of shifted inflation with an SU(5) GUT, see Ref [17]…”
mentioning
confidence: 99%
“…In this paper, we have studied phase transition driven by Hubble-induced mass in supersymmetric F-term inflation models 10 . We have found that in supersymmetric F-term inflation models the breaking scale of GUT and other intermediate symmetry group, which is associated with the production of monopoles and domain walls, are constrained to be larger than the Hubble scale during inflation, because the Hubble-induced mass inevitably arises in supersymmetric F-term inflation models [18].…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Let us summarize the results of this section for the model given by ( 9) and (10). i) The case of M < 10 13 κ −1 GeV is incompatible with the standard cosmological scenario because monopoles would overclose the Universe.…”
Section: B Constraints On the Model Parametermentioning
confidence: 97%
See 2 more Smart Citations